EMERGING CHALLENGES INCOMPETENCY MAPPING AND ITS BENEFITS - AN EMPIRICAL RESEARCH AMONG SUPERVISORS IN TEXTILE MILLS AT ERODE - P.KAMALANATHAN,; N. KUMARASAMY,; K.V.KANNAN, (International Journal of Psychosocial Rehabilitation, 2020)
Even though the interchangeably usage of the phrase competence and competency those are not equal. Competence is a universal term relating to a person’s typical ability, even as competency refers to unique competencies. In today’s competitive environment, people are the most unique and valuable resource for any organizations. These resources cannot be duplicated as every individual is unique. Hence, it is critical for the organizations to make use of this talent to gain the competitive advantage. It is feasible for the organization to become aware of the employee’s talents, attitudes and overall performance through competency mapping. This technique helps to understand the knowledge of the employee, skills and various attributes that are required to perform the organization task efficiently. It is need in all the production/manufacturing companies especially textile industry. Particularly Erode district has selected for this research because of its textile hub. Two textile mills are selected for this research. In this selected textile mills, 103 supervisors have been selected for examining the competency performance. A well-structured questionnaire has been framed and used for the collection of opinion of the supervisors about their performance in competency level. Statistical tools like percentage analysis,mean score analysis, analysis of variance, and multiple regression analysis have been employed. The results showed that 30-40 years aged male supervisors have challenged their job in an efficient way.